The use of U-isotopes on the study of a weathered cover in Parana basin, Brazil - Jimenez-Rueda, JR; Bonotto, Daniel Marcos [UNESP] (A A Balkema Publishers, 2001)
This paper describes the results of a study involving the sampling of a soil profile developed over sandstone from Itarare Sub-Group at the Parana sedimentary basin, Brazil. It was carried out to integrate chemical and U-isotopes data in order to improve the knowledge of the weathering processes acting in the area. U-238 and its daughter U-234 proved to be important tools for evaluating physical and chemical alteration, allowing to suggest a possible timescale for the development of the more superficial soil horizons.